2022
DOI: 10.1002/vms3.1061
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous infection with Ehrlichia Canis and Hepatozoon Canis in dogs from Serbia

Abstract: Background The epidemiological status concerning many canine tick‐borne diseases (TBDs) in Serbia is still insufficiently known. Objectives Our study aimed to investigate the presence of tick‐borne pathogens of the family Anaplasmataceae and Hepatozoon spp., as a cause of illnesses accompanied by clinical signs that can occur in dogs with anaplasmosis, ehrlichiosis and hepatozoonosis. Methods Dogs are included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Additionally, in our study there was no significant difference observed in the MCV, MCH, or MCHC values in the infected animals compared to healthy animals. The current data, are consistent with the results of Sukara et al [21,22,23], which showed normocytic and normochromic anemia in dogs affected with ehrlichiosis. Similar outcomes showing negligible changes in the mean MCV and MCH values were also observed by other workers [15,24,25].…”
Section: Haematological Analysissupporting
confidence: 93%
“…Additionally, in our study there was no significant difference observed in the MCV, MCH, or MCHC values in the infected animals compared to healthy animals. The current data, are consistent with the results of Sukara et al [21,22,23], which showed normocytic and normochromic anemia in dogs affected with ehrlichiosis. Similar outcomes showing negligible changes in the mean MCV and MCH values were also observed by other workers [15,24,25].…”
Section: Haematological Analysissupporting
confidence: 93%
“…Transmission by other arthropods, such as Ehrlichia spp., Anaplasma spp., and Babesia spp. that can carry other pathogens, means that co-infection should also be considered as an aggravating factor of a Hepatozoon canis infection [ 10 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia, a relatively high dispersion of H. canis was observed in different animal species, including the ticks I. ricinus [ 27 ] and R. sanguineus [ 32 ], dogs [ 33 , 34 ], red foxes [ 30 ], wolves [ 21 ], and A. flavicollis mice [ 35 ]. A high prevalence of H. canis was detected in golden jackals in Europe [ 33 , 36 ], as well as in wolves in Serbia (57.94%) [ 21 ], Germany (46%) [ 37 ], and Italy (75.8%) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%